Enhanced radiation resistance of near-infrared photoluminescence emission induced by Er/Si nanoclustering. (15th July 2017) - Wang, C.; Barba, D.; Slim, S.; Wang, Y.Q.; Rosei, F.
Abstract: The influence of Er and Si nanoclustering on near-infrared (NIR) Er emission is investigated in fused silica samples exposed to proton beams, used to reproduce the space radiation conditions at low-Earth orbit (LEO). Bulk silica glasses are used as model systems that mimic optical fibers. The growth of Er/Si nanoclusters, synthesized in co-implanted fused silica after thermal annealing between 1000 °C and 1200 °C, was analyzed by transmission electron microscopy (TEM) and energy-dispersive x-ray spectroscopy analysis. Photoluminescence measurements of Er 3 + optical emission indicate that its 4 I13/2  →  4 I15/2 transition around 1.54 μm can still be used for optical communication after proton irradiation doses equivalent to over 50 years of exposure at LEO. Using a phenomenological model supported by Monte Carlo simulations, our results can be described in terms of an increase of the photocarrier transfer occurring between Si nanocrystals and NIR Er emitting levels, which partially compensates for the optical losses induced by structural damage. Our work demonstrates an alternative approach for the development of advanced Er light sources with superior radiation resistance and longer operating times in space environment. Graphical abstract: Highlights: The structure of Er- and Si-based nanoclusters synthesized by ion implantation and thermal annealing inside silicon dioxide have been investigated at atomic scale. H + bombardment experiments were used to reproduce space environment, followed by optical measurements that shed light on the decay of the 1.54 µm Er emission after radiation exposures. Due to the occurrence of photocarrier transfers between Si and Er nanoparticles, the photoemission of Si/Er systems survives longer to proton irradiations. This result makes the Si/Er systems attractive for the development of new radiation resistant light sources.